2021
DOI: 10.1021/acsabm.1c00426
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Poly(N-Vinylpyrrolidone) Nanoparticles Loaded with DNA Plasmids Encoding Gn and Gc Glycoproteins of the Rift Valley Fever Virus: Preparation and In Vivo Evaluation

Abstract: The aim of the study was to develop amphiphilic poly(N-vinylpyrrolidone) (PVP) nanoparticles (NPs) loaded with DNA plasmids encoding Gn and Gc glycoproteins of the Rift Valley fever virus (RVFV) and to study the humoral response in vivo. DNA plasmids were protected from extracellular nucleases by loading in NPs from PVP derivatives modified with amino acids βalanine (Ala7-PVPOD4000) or glycine (Gly7.5-PVP-OD4000) fabricated by the original self-assembly technique. The obtained NPs were administered in mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Likewise, PVPs have been used to modify liposomal membranes, increasing their stability [ 8 ]. Both in vitro and in vivo assessments of our Amph-PVP nanoparticles showed excellent biocompatibility and safe administration at even high doses [ 9 , 10 , 11 , 12 ], verifying, thus, their application potential. Notably, the utilization of some poly- N -PVP-based carriers have been approved for clinical studies [ 13 ].…”
Section: Introductionmentioning
confidence: 67%
“…Likewise, PVPs have been used to modify liposomal membranes, increasing their stability [ 8 ]. Both in vitro and in vivo assessments of our Amph-PVP nanoparticles showed excellent biocompatibility and safe administration at even high doses [ 9 , 10 , 11 , 12 ], verifying, thus, their application potential. Notably, the utilization of some poly- N -PVP-based carriers have been approved for clinical studies [ 13 ].…”
Section: Introductionmentioning
confidence: 67%
“…Biodegradable alginate (ALG)/poly-L-lysine (PLL) microcapsules (MC), which are polycations used for fabrication of multilayer microcapsules, have been used to deliver DNA vaccines expressing Gn and Gc against RVFV, and results showed that this system enhanced specific-antibody and nAbs titers ( Table 2 ) ( Selina et al., 2020 ). The nanoparticles poly(N-vinylpyrrolidone) (PVP) can form complexes both with low molecular weight substances and polymers, and found to enhance humoral responses against Gn and Gc ( Table 2 ) ( Kuskov et al., 2021 ).…”
Section: Vaccines Against Rvfvmentioning
confidence: 99%
“…In addition to drug delivery, PVP-based nanocarriers can also be used in gene-delivery applications, as demonstrated in a recent study by Selina et al 64 There, the authors described the synthesis of a PVP derivative by a thiyl radical-initiated polymerization to afford PVP followed by chemical modifications on the sidechain to append β-alanine and glycine moieties (Scheme 10). Aside from conferring hydrophilic and antifouling properties, the pyrrolidone moiety also provides a handle for further chemical elaboration, as was the case in this study.…”
Section: Antifouling Stealth Polymers In Nanomedicinementioning
confidence: 99%